A TRANSSHIPMENT MINIMIZATION MODEL FOR BUA MANUFACTURING INDUSTRY (FULafia Journal of Science and Technology, 2021)
Establishing an optimal distribution plan for BUA Cement manufacturing industries has remained a challenge due to the frequent fluctuations of cost of transporting cement. This research revealed a Transportation Optimization Model for cement distribution using Transportation Distance Matrix instead of Transportation Cost Matrix. The study optimized the transportation distance of cement with special interest from two plants namely; Cement Company of Northern Nigeria (Kalambaina, Sokoto) and BUA (Okpella, Edo State) while Sokoto, Kebbi, Zamfara, Kano, Kaduna and Katsina States in Nigeria and as well as Niger Republic were identified as distribution centers. The result of the findings using the Vogel Approximation Method, minimized  the total transportation distance and by implication the total transportation costs.
Keywords: Transshipment; Minimization Model; Distance Matrix; Supply and Demand